The dynamics of students’ accommodation spaces : implications for the acquisition of pedagogical content knowledge - Mhlongo, Hlengiwe Romualda; Nongalo, Noloyiso; Linake, Manthekeleng Agnes (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article aims to explore the dynamics of students’ accommodation spaces and implications on the acquisition of pedagogical content knowledge. The implication of students’ lacking conducive accommodation to learn and live in is a worrying concern, and it need immediate attention as it contributes to their performance. The paper employed a qualitative approach, adopted an interpretive lens, underpinned the Risk Environment Theory; and data were collected through the use of focus group semi-structured interviews. The convenience sampling procedure was followed to select 6 students as participants from three South African universities, participants were B.Ed. students of different levels selected from the faculties of education. Data were analysed using Thematic Analysis. Findings revealed that the lack of proper accommodation for students contributes to their poor performance in academic activities. Findings also showed that if students are provided with decent, safe and affordable accommodation, they have less stress and that makes them fully focus on their studies. In addition, the findings revealed that the students complained of regular break-ins and loss of their gargets and other personal valuable belongings. They further mentioned the issue of water cut, that is on and off around the campuses. This resulted to poor sanitation and unhygienic conditions. All these affect students’ acquisition of pedagogical content knowledge as they get to classes very late or end up missing other morning lectures. It can be concluded that, this challenge of the shortage of students’ accommodation could result to negative implications that include underperfomance and dropiing out of students if it does not receive the urgent attention it deserves.